2021
DOI: 10.3390/microorganisms9081665
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antimicrobial Susceptibility Profiles of Gram-Positive Anaerobic Cocci Responsible for Human Invasive Infections

Abstract: The aim of this multicentre study was to determine the in vitro susceptibility to anti-anaerobic antibiotics of Gram-positive anaerobic cocci (GPAC) isolates responsible for invasive infections in humans. A total of 133 GPAC isolates were collected in nine French hospitals from 2016 to 2020. All strains were identified to the species level (MALDI-TOF mass spectrometry, 16S rRNA sequencing). Minimum inhibitory concentrations (MICs) of amoxicillin, piperacillin, cefotaxime, imipenem, clindamycin, vancomycin, lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 45 publications
1
17
0
Order By: Relevance
“…The results of bacterial identification showed that Anaerococcus prevotii was a gram-positive, anaerobic bacteria and was also described as a common resident of the normal flora of the skin, the oral cavity and the gut [15] . Previous studies have shown that Anaerococcus prevotii is sensitive to metronidazole, and AST is used for confirmation before its use [16] , [17] . Usually, “triple high dose” antibiotics are recommended intravenously for 2 weeks, followed by 4 weeks of oral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The results of bacterial identification showed that Anaerococcus prevotii was a gram-positive, anaerobic bacteria and was also described as a common resident of the normal flora of the skin, the oral cavity and the gut [15] . Previous studies have shown that Anaerococcus prevotii is sensitive to metronidazole, and AST is used for confirmation before its use [16] , [17] . Usually, “triple high dose” antibiotics are recommended intravenously for 2 weeks, followed by 4 weeks of oral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced affinity to target molecule PBP alterations (Gajdacs et al, 2017) b-lactams target site mutation Methylation of the 23S rRNA: ermA, ermB, ermF, and ermTR (Reig et al, 2001;Guerin et al, 2020;Guerin et al, 2021) Nitroimidazole reductase: nimB (Theron et al, 2004) Macrolides Metronidazole…”
Section: Related Research Related Drugsmentioning
confidence: 99%
“…Overall, 7% of the strains were resistant to penicillin and/or clindamycin ( Brazier et al., 2008 ), even though it is widely accepted that GPAC species retain much greater susceptibility to cephalosporins, carbapenems, chloramphenicol, and β-lactam/β-lactamase inhibitors. Generally speaking, GPAC exhibit varying resistance to penicillins (2–25%), clindamycin (3–24%), and metronidazole (3–15%) while having a much greater susceptibility to β-lactam/β-lactamase inhibitors, cephalosporins, carbapenems, and chloramphenicol ( Hastey et al., 2016 ; Yunoki et al., 2017 ; Byun et al., 2019 ; Cobo et al., 2019 ; Badri et al., 2019 ; Forbes et al., 2021 ; Guerin et al., 2021 ).…”
Section: Antibiotic Resistance Of Several Prominent Toa Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial resistance among anaerobes is witnessing a significant upsurge in the recent years worldwide [ 5 ]. Though, GPAC are usually susceptible to commonly used anaerobic antimicrobials, increasing resistance trends and significant difference in susceptibility profile among different species of GPAC have been reported in literature [ 5 , 6 ]. Variable resistance to penicillin (7–10%), metronidazole (5–10%) and clindamycin (7–20%) have been reported amongst GPAC [ 1 , 7 ].…”
Section: Introductionmentioning
confidence: 99%